PENDEKATAN ETNOMATEMATIKA MENGGUNAKAN MAKANAN TRADISIONAL WAJIK SEBAGAI BAHAN AJAR MATEMATIKA PADA MATERI SEGI EMPAT DAN SEGITIGA - Junianti, Ika Wulan; Annisa, Choirul (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2024)
Wajik usually served at weddings on Tuban. The existence of wajik made researcher interested in developing teaching materials that include cultural elements in mathematics learning. The hope of ethnomathematics-based teaching materials can understand mathematical material and introduce our culture to students. The aim of the research was to develop student worksheets with an ethnomathematics approach using wajik traditional food for mathematics learning at seventh grade of junior school on appropriate quadrilaterals and triangles. The method used in this research was Development Research (DR) with the Tessmer research model which consists of two stages, namely preliminary and formative evaluation. The subjects in this research were seventh grade students at SMPN 1 Bancar with trials at the one to one stage with 2 students, the small group stage with 6 students, and the field test stage with 32 students. Validity was obtained based on expert validation results, namely 85%, practicality was obtained based on student response results, namely 93%, and effectiveness was obtained based on student evaluation results, namely 92%. Based on the percentage obtained, the eligibility of the developed worksheet was guaranteed to be feasible.